Translanguaging as a class/lecture-room language management strategy in multilingual contexts: Insights from autoethnographic snapshots from Kenya and South Africa. Issue 3 (30th September 2016) - Mwaniki, Munene
Abstract: The article explores complementary aspects of two nascent developments in (socio) linguistics, namely translanguaging and language management using auto-ethnographic snapshots from class/lecture-room contexts in Kenya and South Africa. Translanguaging entails recognition of a full account of speakers' discursive resources, which posits that 'languages are not sealed units with distinguishable boundaries, nor are they capable of being forced into boxes'. Instead, languages overlap one another in a continuum of discursive resources that are naturally available to multilingual speakers. Language management, on its part, is defined as a paradigm in the sociology and politics of language that seeks to achieve and deepen theoretical adequacy of language policy and planning epistemology and its application(s), especially in multilingual settings, with a view of developing and deploying optimal frameworks and strategies that harness and optimise language resources in society, with the ultimate aim of enlarging people's choices. In line with an extensive corpus of literature that indicates that translanguaging optimises linguistic repertoires of interlocutors, especially in multilingual contexts, the discussion argues that this core character of translanguaging aligns it with the epistemic nexus of language management. The discussion tests and validates this core hypothesis through three autoethnographic snapshots from Kenya and South Africa.